2020
DOI: 10.21203/rs.3.rs-30602/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Changes of serum zinc-α2-glycoprotein level and analysis of its related factors in gestational diabetes mellitus:a cross-sectional study

Abstract: Background Previous studies have discovered that zinc-α2-glycoprotein is related to insulin resistance and lipid metabolism. The aim of the study is to explore the change of serum zinc-α2-glycoprotein(ZAG) and its related factors in gestational diabetes mellitus(GDM). Methods Eighty newly diagnosed GDM patients were enrolled in study group, and 80 normal pregnant women were selected as control group. The differences of baseline data between the two groups were compared, and the change of serum ZAG level and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
(18 reference statements)
0
0
0
Order By: Relevance
“…Feng et al reported serum zinc levels of 43.9 ± 14.5 and 62.5 ± 19.0 mg/L in pregnant women with GDM and controls, respectively (P < 0.001). Also, in this study, there was a significant relationship between serum zinc levels and indices such as gestational age (P < 0.03), diastolic blood pressure (P < 0.001), height, and insulin resistance (P < 0.001), which was in line with the findings of another study (18). In Mishu et al's study, serum zinc levels were significantly lower in GDM women compared to healthy pregnant women, who had normal glucose levels in the second and third trimesters of pregnancy.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Feng et al reported serum zinc levels of 43.9 ± 14.5 and 62.5 ± 19.0 mg/L in pregnant women with GDM and controls, respectively (P < 0.001). Also, in this study, there was a significant relationship between serum zinc levels and indices such as gestational age (P < 0.03), diastolic blood pressure (P < 0.001), height, and insulin resistance (P < 0.001), which was in line with the findings of another study (18). In Mishu et al's study, serum zinc levels were significantly lower in GDM women compared to healthy pregnant women, who had normal glucose levels in the second and third trimesters of pregnancy.…”
Section: Discussionsupporting
confidence: 92%
“…Wang et al showed that the mean level of serum zinc in pregnant women with BMIs less than 18 kg/m 2 was lower than in peers with normal BMIs (15). Variabilities in the findings of these studies can be due to different factors, including different cut-off points used to define zinc deficiency, age differences between the studied populations, as well as variations in economic status, gestational age, and the sample size (18).…”
Section: Discussionmentioning
confidence: 99%